«ΧΑΜΕΝΟΙ ΣΤΗ ΜΕΤΑΦΡΑΣΗ»: ΕΡΕΥΝΑ ΣΤΙΣ ΝΕΟΕΛΛΗΝΙΚΕΣ ΔΗΜΟΣΙΕΥΜΕΝΕΣ ΚΑΙ ΑΔΗΜΟΣΙΕΥΤΕΣ ΜΕΤΑΦΡΑΣΕΙΣ ΑΡΧΑΙΟΥ ΔΡΑΜΑΤΟΣ [LOST IN TRANSLATION. RESEARCHING THE PUBLISHED AND NON-PUBLISHED TRANSLATIONS OF ANCIENT GREEK DRAMA] - Diamantakou, Kaiti; Delipetrou, Evdokia; Damaskinos, Manos; Cohen, Alexandros (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
This publication presents a summary of the aim, scope, methodology, personnel, and the initial quantitative and qualitative findings related to two complementary, funded research projects. Although formally completed, these projects continue to operate institutionally and substantially within the Laboratory of Ancient Drama and Theatrological Research (L.AN.D.THE.RE.) of the NKUA Department of Theatre Studies. The projects are: «Translations of Ancient Drama in the New Millennium» (Μεταφράσεις Αρχαίου Δράματος στη Nέα Xιλιετία) and «Unpublished Translations of Ancient Drama: Location – Cataloguing – Collection – Evaluation» (Αδημοσίευτες μεταφράσεις αρχαίου δράματος: Εντοπισμός – Καταγραφή – Συγκέντρωση – Αξιολόγηση). Both are conducted under the scientific supervision of Kaiti Diamantakou, Professor at the NKUA Department of Theatre Studies, and their research teams include the co-authors of this publication: Evdokia Delipetrou, Manos Damaskinos, and Alexandros Cohen.